COOPERATIVE LEARNING IN THE BRAZILIAN ACADEMIC EDUCATIONAL SCENARIO - Silveira Bello, Marcia Miranda; Messias Fialho Capellini, Vera Lucia [UNESP]; Garcia Ribeiro, Job Antonio (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
The present study aimed at knowing, systematizing and discussing the Brazilian production related to Cooperative Learning (CA). In order to select the works that explicitly refer to the theme in the context of face-to-face teaching, the following bibliographic sources were used: annals / congress minutes, periodicals (Qualis A1, A2, B1 and B2 journals in the areas of Education and Teaching), theses and dissertations. Through the descriptors cooperative or cooperative, 47 studies were identified, combined between the terms learning, method and work, distributed between 2002 and 2016. Most of them were empirical (85.1%). It was identified, in addition to a growing trend of research on the subject, that the CA is adopted in different educational modalities (formal and non-formal education) and levels of education (predominantly in Higher Education and High School). Its use with the intention of enhancing the learning processes of content is the most frequent and occurs mainly in the area of Exact Sciences and Earth. It was also observed that the Southeast and Northeast regions of the country concentrate the majority of studies performed. In addition to contributing to the dissemination of the AC, it is intended that this work, based on the outline map, subsidizes new research that corroborates the use of this approach in teaching educational practice at different levels of education, since it is also a question of way of philosophical, ethical and pedagogical thinking.
Keywords: cooperative learning; state of art; literature review